System dynamics modelling as policy decision support for retaining and recycling water within the urban water system to address water scarcity – the case of the City of Cape Town - Van Zyl, Amore (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.